Reinstating fiscal policy for normal times: Public investment and Public Jobs Programmes - Gasperin, Simone; Skidelsky, Robert (PSL Quarterly Review, 2021)
This paper upholds the classical Keynesian position that a laissez-faire market economy lacks a spontaneous tendency to full employment. Focusing on the UK case, it argues that monetary policy could not prevent the economic collapse of 2008-9 or achieve full recovery from the Great Recession that followed. The paper then outlines the case for fiscal policy to regain a permanent status of primacy in modern macroeconomic management, beyond the pandemic emergency. It distinguishes between public investment and automatic stabilisers, reducing discretionary actions to a minimum. It presents the case for re-empowering the State’spublic investment function and for reforming the system of automatic counter-cyclical stabilisers by means of public jobs programmes. JEL codes: E32, E52, E61, E62, E63, H54, J68 Keywords: monetary policy, fiscal policy, public investment, job programmes